2021
DOI: 10.1155/2021/4339451
|View full text |Cite
|
Sign up to set email alerts
|

Residual Quantitative Flow Ratio to Estimate Post‐Percutaneous Coronary Intervention Fractional Flow Reserve

Abstract: Objectives. Quantitative flow ratio (QFR) computes fractional flow reserve (FFR) based on invasive coronary angiography (ICA). Residual QFR estimates post‐percutaneous coronary intervention (PCI) FFR. This study sought to assess the relationship of residual QFR with post-PCI FFR. Methods. Residual QFR analysis, using pre-PCI ICA, was attempted in 159 vessels with post-PCI FFR. QFR lesion location was matched with the PCI location to simulate the performed intervention and allow computation of residual QFR. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Previous landmark studies have demonstrated the instrumental value of the QFR in guiding the PCI procedure and further improving the clinical prognosis ( 10 12 ). The residual QFR is a predicted QFR value based on coronary angiographic imaging that simulates successful stent implantation in the culprit lesion, correlates well with the post-PCI FFR and QFR, and predicts the occurrence of adverse events after revascularization ( 13 , 14 , 16 , 22 ). A retrospective analysis of the PANDA III trial showed that the predicted clinical outcome of residual QFR-guided PCI was superior to that of angio-guided PCI ( 15 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous landmark studies have demonstrated the instrumental value of the QFR in guiding the PCI procedure and further improving the clinical prognosis ( 10 12 ). The residual QFR is a predicted QFR value based on coronary angiographic imaging that simulates successful stent implantation in the culprit lesion, correlates well with the post-PCI FFR and QFR, and predicts the occurrence of adverse events after revascularization ( 13 , 14 , 16 , 22 ). A retrospective analysis of the PANDA III trial showed that the predicted clinical outcome of residual QFR-guided PCI was superior to that of angio-guided PCI ( 15 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stent diameter in the underanticipated group in this study was smaller (2.96 ± 0.41 vs. 3.11 ± 0.44, P = 0.004) than that in the consistent group, supporting the previous hypothesis. A low residual QFR suggests that the target vessel may have a limited or diffuse lesion that the operator is unaware of or that the benefit of intervention for this coronary lesion is low, and this information may help to modify the PCI strategy ( 14 ). In addition, compared with the consistent group, the overanticipated group had a greater mean number of stents implanted (1.65 ± 0.62 vs. 1.23 ± 0.45, P < 0.001) and a longer total stent length (43.42 ± 17.47 vs. 30.80 ± 13.66, P < 0.001), which may have contributed to the greater post-PCI QFR than residual QFR in the overanticipated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, residual QFR predicts the results of a technically successful angioplasty and does not fully consider potential issues (such as stent under-expansion in severely calcified vessels) that can worsen the PCI results and impair actual post-PCI functional values. Another retrospective analysis with wider inclusion criteria was provided by Van Diemen et al [33], with all kinds of lesions suitable for post-PCI FFR and residual QFR evaluation. Correlation between residual QFR and FFR was good (r = 0.56), but again these results did not fully reflect common clinical practice, because post-PCI functional evaluation was performed only in the case of "successful angioplasty" defined by the operators.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies presented the feasibility of computed tomography–derived FFR or functional coronary angiography with virtual pullback technology in procedural planning. 86 , 91 , 92 Upcoming trials in this field will provide further data on the use of these methods. The AQVA (Angio-based quantitative flow ratio virtual PCI versus conventional angio-guided PCI in the achievement of an optimal post-PCI QFR; NCT04664140 ) study investigators are comparing QFR-based virtual PCI with conventional angiography–guided PCI in a prospective randomized fashion.…”
Section: Longitudinal Vessel Analysis and Procedural Planningmentioning
confidence: 99%